Assembly and Succession of Iron Oxide Microbial Mat Communities in Acidic Geothermal Springs - Beam, Jacob P.; Bernstein, Hans C.; Jay, Zackary J.; Kozubal, Mark A.; Jennings, Ryan deM.; Tringe, Susannah G.; Inskeep, William P. (Frontiers in Microbiology, 2016)
Biomineralized ferric oxide microbial mats are ubiquitous features on Earth, are common in hot springs of Yellowstone National Park (YNP, WY, USA), and form due to direct interaction between microbial and physicochemical processes. The overall goal of this study was to determine the contribution of different community members to the assembly and succession of acidic high-temperature Fe(III)-oxide mat ecosystems. Spatial and temporal changes in Fe(III)-oxide accretion and the abundance of relevant community members were monitored over 70 days using sterile glass microscope slides incubated in the outflow channels of two acidic geothermal springs (pH = 3 - 3.5; temperature = 68 - 75 °C) in YNP. Hydrogenobaculum spp. were the most abundant taxon identified during early successional stages (4 - 40 d), and have been shown to oxidize arsenite, sulfide, and hydrogen coupled to oxygen reduction. Iron-oxidizing populations of Metallosphaera yellowstonensis were detected within 4 d, and reached steady-state levels within 14 - 30 d, corresponding to visible Fe(III)-oxide accretion. Heterotrophic archaea colonized near 30 d, and emerged as the dominant functional guild after 70 d and in mature Fe(III)-oxide mats (1 - 2 cm thick). First-order rate constants of Fe(III)-oxide accretion ranged from 0.046 - 0.05 d-1, and in situ microelectrode measurements showed that the oxidation of Fe(II) is limited by the diffusion of O2 into the Fe(III)-oxide mat. The formation of microterracettes also implicated O2 as a major variable controlling microbial growth and subsequent mat morphology. The assembly and succession of Fe(III)-oxide mat communities follows a repeatable pattern of colonization by lithoautotrophic organisms, and the subsequent growth of diverse organoheterotrophs. The unique geochemical signatures and micromorphology of extant biomineralized Fe(III)-oxide mats are useful for understanding other Fe(II)-oxidizing systems.